No App is an Island: Collective Action and Sustainable Development Goal-Sensitive Design - Pitt, Steph; van Meelis Lacey, Marlína; Scaife, Ed; Pitt, Jeremy (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2022)
The transformation to the Digital Society presents a challenge to engineer ever more complex socio-technical systems in order to address wicked societal problems. Therefore, it is essential that these systems should be engineered with respect not just to conventional functional and non-functional requirements, but also with respect to satisfying qualitative human values, and assessing their impact on global challenges, such as those expressed by the UN sustainable development goals (SDGs). In this paper, we present a set of sets of design principles and an associated meta-platform, which focus design of socio-technical systems on the potential interaction of human and artificial intelligence with respect to three aspects: firstly, decision-support with respect to the codification of deep social knowledge; secondly, visualisation of community contribution to successful collective action; and thirdly, systemic improvement with respect to the SDGs through impact assessment and measurement. This methodology, of SDG-Sensitive Design, is illustrated through the design of two collective action apps, one for encouraging plastic re-use and reducing plastic waste, and the other for addressing redistribution of surplus food. However, as with the inter-connectedness of the SDGs, we conclude by arguing that the inter-connectedness of the Digital Society implies that system development cannot be undertaken in isolation from other systems.
Keywords: socio-technical systems; value-sensitive design; collective action; plug-in architecture; sustainable development goals; IJIMAI